2015
DOI: 10.1039/c5ra01826a
|View full text |Cite
|
Sign up to set email alerts
|

Redox-economical radical generation from organoborates and carboxylic acids by organic photoredox catalysis

Abstract: Redox-economical radical reactions by organic photoredox catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 44 publications
1
64
0
1
Order By: Relevance
“…Recent total synthesis endeavors in our laboratories have suggested the potentially broad utility of both trialkyl-tertiary cuprates and nucleophilic carbon radicals in such constructions. 1,2,3 Tertiary carbon radicals are often generated from halide precursors. However, the synthesis of structurally elaborate tertiary halides can be complicated by competing elimination and rearrangement reactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent total synthesis endeavors in our laboratories have suggested the potentially broad utility of both trialkyl-tertiary cuprates and nucleophilic carbon radicals in such constructions. 1,2,3 Tertiary carbon radicals are often generated from halide precursors. However, the synthesis of structurally elaborate tertiary halides can be complicated by competing elimination and rearrangement reactions.…”
Section: Introductionmentioning
confidence: 99%
“…1c To extend this approach to other readily available precursors, we recently described the utility of N -phthalimidoyl oxalate derivatives of tertiary alcohols for generating tertiary radicals using visible-light photocatalysis. 3b …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47] In this Scheme 25. Metal-and oxidant-free cyanation using alkyltrifluoroborates and suggested mechanism.…”
Section: C(sp 3 )-Organoboron Substratesmentioning
confidence: 99%
“…Later, Akida and co-workers demonstrated that this transformation can also be accomplished with the organic photocatalyst 21 (see Scheme 10B). [47] Scheme 12. Ir-catalyzed radical decarboxylative Giese-type addition with alkyl carboxylic acids and suggested mechanism.…”
Section: C(sp 3 )-Cooh and Derivatives Thereofmentioning
confidence: 99%